Three new species of Oxysarcodexia Townsend (Diptera: Sarcophagidae)from the Colombian Andes - Souza, Carina Mara De; Buenaventura, Eliana (Zootaxa, 2016)
Three new species of Oxysarcodexia Townsend (Diptera: Sarcophagidae) from the Colombian Andes are described based on male specimens collected using decaying animal matter as bait: Oxysarcodexia catica sp. n., O. laclaricola sp. n., and O. liliarum sp. n. The straight and narrow cercal prong with an acute apex, and the juxta enlarged distally and folded backwards of O. catica sp. n. resemble these structures in O. fraterna Lopes, O. peruviana (Lopes) and O. vittata (Walker). The shape of the cercus of O. laclaricola sp. n. is similar to that of O. floricola Lopes, whereas its vesica is similar in shape to that of O. cyaniforceps (Hall). Oxysarcodexia liliarum sp. n. resembles O. favorabilis (Lopes) in the inflorescence-like phallus and enlarged juxta. The postero-distal phallic enlargement of O. catica sp. n. and O. liliarum sp. n. support the inclusion of these species in the so-called “Xarcophaga group” (sensu Lopes).